Analisis Implementasi Peraturan Daerah Kota Bekasi Nomor 09 Tahun 2019 Tentang Penyelenggaraan Lalu Lintas Dan Angkutan Jalan Kota Bekasi - Wulandari, Hadi; Setiawan, Dodi Rahmat; Zulkifli, Zulkifli (Jurnal Ilmu Administrasi Publik, 2024)
The focus of this research is the implementation of the Bekasi City Regional Regulation Number 09 of 2019 concerning the Implementation of Road Traffic and Transportation which is the responsibility of the Bekasi City Transportation Service in the Implementation of Road Equipment. To measure the success of Implementation by applying the Edward III Model which includes Communication, Resources, Disposition and Bureaucratic Structure.   This study aims to analyze what factors support and hinder successful implementation. This study uses a qualitative research approach with descriptive research types. Data collection techniques through interviews, observation, documentation and triangulation. Determination of informants using nonprobability purposive sampling technique. Data analysis techniques use descriptive data analysis techniques.   The results of the study show that the implementation of the Bekasi City Regional Regulation Number 09 of 2019 has generally been going well.   Supporting factors include communication that runs very well, support for the attitude of policy implementers and relationships between work units that are very well established making it easier to coordinate and work together. While the inhibiting factors are human resources and limited budget.